Kadar Optimum Aspal Pen 60/70 dan Bahan Modifikasi Asbuton Murni T5/20 Dengan Filler Asbuton T5/20 terhadap Kinerja Campuran - fitra ramdhani (Racic : Rab Construction Research, 2018)
In line with the increase in road length, the asphalt demand in Indonesia is increasing as well. Asbuton can be used as a binder on pavement to replace oil asphalt. The levels of asphalt contained in asbuton is variated between 10% -40%. To increase the utilization of asbuton in Indonesia, the research on modification of asbuton in the mixture was carried out. This study aims to determine the optimum levels of bitumen pen 60/70 and material modification of pure asbuton T5 / 20 with filler asbuton T5 / 20 against on mixture performance. This research was carried out by adding optimum asbuton filler level of 2.01% on the variation of pure T5 / 20 asbuton by 0%, 10%, 12%, 14%, 16%, 18%, 20% and 30% with a compaction temperature of 155 0C in mixture. Based on the results of the Marshall test, the performance of the modified material mixture that meets the general specification requirements on Bina Marga 2010 revision 3 which is the optimum level of extraction of asphalt T5 / 20 by 10% with filler asbuton T5 / 20 of 2.01%. This is evidenced by the Stability value of 2616 kg, the melting value of 2.85 mm, MQ value of 918 kg / mm, VIM value of 4.94%, VMA value of 15% and VFA value of 66.11% that meets the specification requirements.